Updated records for Leptophlebiidae (Ephemeroptera) and a new species of Thraulodes Ulmer, 1920 from Tocantins State, Northern Brazil - Orlando, Thales Yann; Salles, Frederico Falcão; Boldrini, Rafael; Krolow, Tiago Kütter (Zootaxa, 2021)
An annotated checklist with complementary information for leptophlebiid mayflies from Tocantins State, Brazil is provided. Additionally, we describe a new species of Thraulodes Ulmer, 1920 based on male adults. New reports are based on collections conducted between August 2017 and August 2019 in 13 localities of 10 municipalities. A total of 436 adults distributed in 11 genera, 16 species and five morphospecies treated as undescribed species were collected. Of the total species examined, 11 are new records.